NEEDS ASSESSMENT OF INFORMATION AND COMMUNICATION TECHNOLOGY COMPETENCIES IN THE TWENTY–FIRST CENTURY OF SCHOOL ADMINISTRATORS UNDER THE OFFICE OF SECONDARY EDUCATIONAL SERVICE AREA UDON THANI - Pothikoon, Pharichat; Chompuwiset , Patcharin; Choeybal, Panayuth (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The purposes of this research were to examine the actual and expected conditions and needs assessment of Information and Communication Technology (ICT) Competencies in the 21st Century of school administrators. The sample, obtained through stratified random sampling, consisted of 331 teachers working in schools under the Office of Secondary Educational Service Area Udon Thani. The sample size for this research was determined using the Krejcie & Morgan sample size determination table. The research instrument was a 5 rating–scale questionnaire with the IOC ranging from 0.60 to 1.00. The Item–Total Correlation of the actual conditions ranged from 0.43 to 0.88 and from 0.54 to 0.92 for expected conditions, with the reliability of 0.98 and 0.99, respectively. Statistics for data analysis included frequency, percentage, mean, standard deviation, and modified priority needs index (PNI). The findings indicated that the actual conditions of school administrators’ ICT competencies in the 21st Century were overall at a high level, while the expected conditions were rated at the highest level. The Priority Needs Index (PNI) for ICT competencies in the 21st century among school administrators ranked the following aspects in order of priority: Society, Laws, Ethics, Professional Ethics, and Security; Visionary and Leadership; ICT Knowledge and Use, ICT Support, Promotion, and Management, and Communication within Schools, and Support for Learning Management.